Cape Honey Bee Apis mellifera capensis Escholtz - James D. Ellis (EDIS, 2012)
Cape honey bees can produce both male and female offspring parthenogenetically. Unlike other African bee races, they are docile, but unlike all other races of honey bees, they are social parasites. Find out why South African beekeepers consider Cape bees a more serious threat than the varroa mite in this 4-page fact sheet. Written by James D. Ellis and published by the UF Department of Entomology and Nematology, December 2011.